Konsep Uzlah Neo-Sufisme dan Relevansinya Dengan Upaya Menjaga Kesehatan Mental di Era Kontemporer (Kajian Psikosufistik) - Nurul Azizah, Isnawati (Universitas Muhammadiyah Kotabumi, 2024)
Uzlah is one aspect of Sufism that is often seen as negative by some people. They consider that uzlah is an anti-social activity and is considered a disregard for environmental conditions which is full of slander and evil. However, environmental conditions are also a factor that influences mental health. This research attempts to explain the Neo-Sufism concept of uzlah which can be applied in this contemporary era and its relevance to efforts to maintain mental health. Mental health, just like physical or bodily health, must be maintained in order to be able to carry out daily activities well and create a healthy community environment as well. This research is a qualitative research with library research. The approach used is a psychosufistic approach. The results of the discussion in this research found that the concept of uzlah as defined by neo-Sufism (Nurcholis Madjid, Buya Hamka) is exile as an effort to strengthen the mental or soul so that they can develop new strategies and strengths and fortify themselves so that they can fix and improve the social conditions of society, not means running away from society. The use of neo-Sufism, to develop strategies and strengthen the soul, certainly has a very close relevance to maintaining mental health so that it does not become easily fragile amidst the pressures faced in the environment and becoming a more optimistic, positive and visionary human being with the steps outlined in discussion.